Pure Neural Leprosy - Verdy, Verdy; Budiyanto, Arief; Siswati, Agnes Sri (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Pure neural leprosy (PNL) is an infection by Mycobacterium leprae with clinical manifestation as nerve thickening, sensory nerve impairment, with or without motoric nerve involvement, and without skin lesion. Pure neural leprosy causes progressive degeneration of nerve function. Diagnosis establishement of PNL is difficult. Purpose: To discuss about PNL especifically in aspects of the diagnosis and therapy. Reviews: Gold standard in diagnosis of PNL is histopathological examination from nerve biopsy but this procedure is still difficult for various reasons. Some investigations can be done for PNL such as cytological fine needle aspiration, Mitsuda test, serology test for antibody anti-PGL1, electroneuromyography (ENMG), and polymerase chain reaction (PCR). Pure neural leprosy classification is based on findings of abnormality in neurological, immunological, and histopathological. Pure neural leprosy therapy is based on the classification of paucibacillary or multibacillary. Conclusions: The clinical and epidemiological findings plus with the electroneuromyography alteration were finally accepted as sufficient criteria to diagnose PNL. Pure neural leprosy therapy follows WHO regiment in accordance with the paucibacillary or multibacillary classification.Key words: pure neural leprosy, Mycobacterium leprae, nerve biopsy, anti-PGL-1, electroneuromyography.